2007
DOI: 10.1103/physrevb.75.115326
|View full text |Cite
|
Sign up to set email alerts
|

Long-range order in the Bose-Einstein condensation of polaritons

Abstract: We adopt a kinetic theory of polariton nonequilibrium Bose-Einstein condensation to describe the formation of off-diagonal long-range order. The theory accounts properly for the dominant role of quantum fluctuations in the condensate. In realistic situations with optical excitation at high energy, it predicts a significant depletion of the condensate caused by long-wavelength fluctuations. As a consequence, the one-body density matrix in space displays a partially suppressed long-range order and a pronounced d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 38 publications
(92 reference statements)
0
45
0
Order By: Relevance
“…Recently, a similar phase transition has been reported for the lower branch of exciton-polaritons (LPs) in planar semiconductor microcavities [5,6,7,8,9,10,11,12], and supporting theoretical frameworks have been developed [13,14,15,16,17,18,19,20]. Interestingly, LPs are free particles in a two dimensional (2D) system where genuine BEC exists only at zero temperature in the thermodynamic limit [21,22].…”
Section: Pacs Numbersmentioning
confidence: 55%
“…Recently, a similar phase transition has been reported for the lower branch of exciton-polaritons (LPs) in planar semiconductor microcavities [5,6,7,8,9,10,11,12], and supporting theoretical frameworks have been developed [13,14,15,16,17,18,19,20]. Interestingly, LPs are free particles in a two dimensional (2D) system where genuine BEC exists only at zero temperature in the thermodynamic limit [21,22].…”
Section: Pacs Numbersmentioning
confidence: 55%
“…[11][12][13] Recently, it has been suggested that the presence of spatial confinement could have an impact on the thermalization process. 14 This is confirmed by pioneering experimental observations in micropillars, where the spontaneous quantum degeneracy of microcavity polaritons seems to be reached at lower excitation densities than in planar microcavities. 15 In order to clarify this point, a detailed investigation of the efficiency of relaxation and thermalization of polaritons in spatially confined structures is required.…”
Section: Introductionmentioning
confidence: 53%
“…The real part g 0 is associated with an energy renormalization, while the imaginary part g represents the strength of EID, which is also referred to as collisional broadening. The ratio of the constants is estimated as 2g pae /g 0 /6n s E b a 2 0 , where n s is the saturation density of excitons [26]. E b and a 0 are respectively the exciton binding energy and Bohr radius.…”
Section: Theorymentioning
confidence: 99%